An Analysis of Deixis in Joe Biden’s Speech 2024 - Alya Aulia Siregar; Indah Nadine Silvana Situmorang; Nestaria Br Tarigan; Zahara Saputriyani (CV Wahana Publikasi, 2025)
This study analyzes how deixis influenced Joe Biden’s 2024 speech regarding Donald Trump’s electoral victory. This research applies a qualitative descriptive method. Joe Biden’s statement after Donald Trump’s election is important because it had major social and political significance and drew global attention, especially from his linguistic choices. Deictic expressions such as “I,” “you,” “here,” “now,” and “this” derive their meanings entirely on the contextual perspectives of the speaker and listener. The study seeks to ascertain the function of deixis in the context of political speech. The information was gathered from the whole official transcript of American Rhetoric after viewing the speech on the YouTube channel of ABC 7 Chicago. Levinson’s (2001) theory was applied to the transcript in order to identify, categorize, and count all deictic words. The results show that there are five deixis types are identified: person (62.2%), spatial (14.2%), temporal (7.2%), social (10%), and discourse (6.4%). While geographical and social deixis assist tie Biden’s message to actual surroundings and convey respect, the dominance of person deixis shows his attempt to foster unity and intimacy with the audience. In addition to serving as a resource for upcoming linguistic research of political speeches, this study advances our knowledge of how deixis works as a strategic and persuasive instrument in political communication. These findings confirm that deixis plays a vital role in political speech by influencing public perception, improving rhetorical coherence, and bolstering a leader’s identity and authority.